Zinner’s syndrome: to observe or to operate? a triplet of cases with varying clinical presentation - Singh, Anshuman; Reddy, Bommireddy V.; Choudhary, Anupam; K. R., Surag; Chawla, Arun (International Surgery Journal, 2023)
Zinner’s syndrome is a rare condition that can be challenging to diagnose and manage. Limited knowledge about its natural history and optimal treatment further complicates matters. To shed more light on this condition, we present a case series of three patients with Zinner’s syndrome, highlighting their clinical presentations, diagnostic workup, and treatment options. Our first patient was a 16-year-old male with left epididymo-orchitis and left renal agenesis. The second patient was a 25-year-old male with left epididymo-orchitis, left seminal vesicle cyst, and left renal agenesis. The third patient was a 65-year-old male with left seminal vesicle cysts and aplastic ectopic renal tissue with ectopic ureteral insertion into the seminal vesicle cyst causing acute urinary retention. The two patients who presented with epididymo-orchitis were managed conservatively while the one presenting with acute urinary retention required surgical exploration and excision. It is noted that diagnosis of Zinner’s syndrome requires a high index of suspicion, and radiological imaging is crucial for confirmation. Surgical intervention is often necessary to treat symptomatic compression, and fertility counselling is necessary due to the potential for impaired semen quality. Close monitoring is needed due to the risk of renal impairment in the future.